2011
DOI: 10.1590/s0100-204x2011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de acessos do banco de germoplasma de mangaba em Sergipe

Abstract: Genetic diversity of accessions of the mangaba germplasm bank in Sergipe, BrazilAbstract -The objective of this work was to estimate the genetic variability of mangaba accessions of natural populations, from 11 locations, using RAPD markers. The accessions belong to Banco Ativo de Mangaba of Embrapa Tabuleiros Costeiros, in Itaporanga d'Ajuda, SE, Brazil. A total of 13 primers were used, which generated 82 fragments, of which 78 (95%) were polymorphic. Genetic analysis among regions showed low genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 16 publications
6
38
0
17
Order By: Relevance
“…The absolute values were 0.207 (Region 1), 0.197 (Region 2), and 0.229 (Region 3). These results are close to those obtained in studies with dominant markers in natural populations; for example, 0.163-0.236 for Eugenia dysenterica (Zucchi, 2002), 0.25-0.29 to Polylepis australis (Julio et al, 2008), 0.11-0.26 and 0.25-o 0.42 for Hancornia speciosa (Costa et al, 2011;Martins et al, 2012), 0.30-0.42 for Acrocomia aculeata (Oliveira et al, 2012), and 0.24-0.27 for Metrodorea nigra (Moraes Filho et al, 2015). In addition, these results are much higher than those obtained for autogamous species such as Theobroma speciosum (Ĥ E = 0.051-0.095; Giustina et al, 2014), and Coffea arabica (Ĥ E = 0.05-0.15; Aga et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…The absolute values were 0.207 (Region 1), 0.197 (Region 2), and 0.229 (Region 3). These results are close to those obtained in studies with dominant markers in natural populations; for example, 0.163-0.236 for Eugenia dysenterica (Zucchi, 2002), 0.25-0.29 to Polylepis australis (Julio et al, 2008), 0.11-0.26 and 0.25-o 0.42 for Hancornia speciosa (Costa et al, 2011;Martins et al, 2012), 0.30-0.42 for Acrocomia aculeata (Oliveira et al, 2012), and 0.24-0.27 for Metrodorea nigra (Moraes Filho et al, 2015). In addition, these results are much higher than those obtained for autogamous species such as Theobroma speciosum (Ĥ E = 0.051-0.095; Giustina et al, 2014), and Coffea arabica (Ĥ E = 0.05-0.15; Aga et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…Indeed, our results showed this low locus variability, with four monomorphic markers and five markers with two or three alleles per locus. The low H E value (0.2) obtained in our analysis is similar to that reported in a previous study (Costa et al, 2011) and suggested low genetic diversity in mangabeira populations. The polymorphic loci are important indicators of the level of genetic variation in a given area.…”
Section: Discussionsupporting
confidence: 91%
“…To date, there have been very few studies of genetic diversity in mangabeira populations, and all of them use RAPD markers as the molecular tool (Moura et al, 2005(Moura et al, , 2011Costa et al, 2011;Silva et al, 2011) due to the absence of the species genome information. As noted, only six sequences of H. speciosa appear in the GenBank database.…”
Section: Discussionmentioning
confidence: 99%
“…The H E values in the present study were similar to those in studies with natural populations, e.g., 0.27 to 0.33 for T. pallida (Zimback et al, 2004), 0.25 to 0.29 for Polylepis australis (Julio et al, 2008), 0.11 to 0.26 for Hancornia speciosa (Costa et al, 2011) and 0.25 to 0.42 for Acrocomia aculeata (Oliveira et al, 2012), suggesting a strong genetic basis.…”
Section: Discussionsupporting
confidence: 89%